2020
DOI: 10.1364/boe.388531
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of two optical quality metrics to predict the visual acuity of multifocal pseudophakic patients

Abstract: This article studies the relationship between two metrics, the area under the modulation transfer function (MTFa) and the energy efficiency (EE), and their ability to predict the visual quality of patients implanted with multifocal intraocular lenses (IOLs). The optical quality of IOLs is assessed in vitro using two metrics, the MTFa and EE. We measured them for three different multifocal IOLs with parabolic phase profile using image formation, through-focus (TF) scanning, three R, G, B wavelengths, and two pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
0
14
0
11
Order By: Relevance
“…Studies on multifocal contact lenses ( Kawamorita and Uozato, 2005 ; Madrid-Costa et al, 2012 ; Fernández et al, 2019 ) found the similar results. MTFa was also used to predict VA and CS of multifocal intraocular lenses ( Vega et al, 2018 ; Armengol et al, 2020 ). In the current study, MTFs and MTFa showed that a concentric ring design impacted less visual performance than the honeycomb design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on multifocal contact lenses ( Kawamorita and Uozato, 2005 ; Madrid-Costa et al, 2012 ; Fernández et al, 2019 ) found the similar results. MTFa was also used to predict VA and CS of multifocal intraocular lenses ( Vega et al, 2018 ; Armengol et al, 2020 ). In the current study, MTFs and MTFa showed that a concentric ring design impacted less visual performance than the honeycomb design.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation transfer function ( Pieh et al, 2002 ; Son et al, 2017 ) has been widely used to quantify the optical quality of the lens design, and MTFa (modulation transfer function area) can be used to predict the VA and CS outcome ( Fernández et al, 2019 ; Armengol et al, 2020 ). In summary, to calculate MTF, one evaluates the complex amplitude in the pupil plane, then using fast Fourier transform (FFT) calculates the point spread function (PSF) and finally the MTF, using one center wavelength (λ = 550 nm) and assuming the pupil position directly on the glass ( Voelz, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…42 Further correlations between the polychromatic EE and clinical average VA of pseudophakic patients have been reported recently. 43 Suchkov et al 44 showed the influence of modifying LCA on VA, both experimentally and by simulation using a chromatic eye model. Although VA exhibits a robust response under modified chromatic conditions, the authors reported impairment in the predictability of the results with an LCA modified from natural conditions, as the experimental VA values were lower than the predicted.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In a study comparing the predictability of MTFa and LIB, both metrics demonstrated a strong correlation with clinical VA (MTFa, R 2 = 0.94; LIB, R 2 = 0.90). 26 However, the predictability of MTFa diminished more rapidly than LIB when increasing pupil size, indicating its sensitivity to pupil dependent aberrations. Further studies are needed to determine whether other optical parameters may have a similar effect on MTFa.…”
Section: Discussionmentioning
confidence: 95%